2017
DOI: 10.18295/squmj.2016.17.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Persian Short-Form Version of a Standardised Questionnaire Assessing Oral Cancer Knowledge, Practice and Attitudes Among Dentists

Abstract: abstract:Objectives: Oral cancer is a global health problem; however, many dentists lack the necessary skills, knowledge and capacity to diagnose oral cancers early. This study aimed to examine the validity and reliability of a Persian short-form version of a standardised questionnaire to assess dentists' knowledge, practice and attitudes towards oral cancer. Methods: This cross-sectional analytical study was carried out in May 2015 in Tehran, Iran. An original 39-item English-language questionnaire developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The reporting of literature review on the KAP key question showed 55 studies using SPIDER and 11 using the PICO tool, divided per categories as follows: 50 among dentists [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ], eight among physicians [ 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reporting of literature review on the KAP key question showed 55 studies using SPIDER and 11 using the PICO tool, divided per categories as follows: 50 among dentists [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ], eight among physicians [ 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies were conducted in America [ 17 , 18 , 22 , 39 , 43 , 50 , 51 , 52 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 65 , 67 , 71 , 73 , 77 , 78 , 81 ], 20 in Europe [ 12 , 27 , 38 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 53 , 54 , 64 , 66 , 68 , 69 , 70 , 72 , 79 , 80 ], 17 in Asia [ 19 , 20 , 23 , 24 , 29 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 40 , 41 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The measurement of a latent trait, a characteristic not directly observable, is done indirectly, through the application of a questionnaire, a tool that allows to evaluate this ability. However, the process of creating this instrument is so complex and time-consuming that some studies even advocate exporting questionnaires to other cultures [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%